Performance Assessment Of High-Rise Building Foundations Subjected To Variable Soil And Load Conditions In Coastal Environments - Dermawan Zebua; Jun Fajar Krisman Giawa; Anggerius Loi; Cristopher Zebua (Journal of Advanced Engineering and Technology Research, 2025)
High-rise buildings in coastal environments are exposed to complex geotechnical and environmental conditions that significantly affect foundation performance. This study evaluates the behavior of high-rise building foundations under variable soil and load conditions using field investigation, laboratory testing, and numerical modeling. Soil stratigraphy, groundwater fluctuations, and load variability were analyzed to assess settlement, differential tilting, and stress distribution. Results indicate that pile foundations outperform mat and combined mat-pile foundations in controlling differential settlement and maintaining structural serviceability. Groundwater level changes and load variations notably influence foundation performance, emphasizing the need for site-specific, performance-based design. The integrated methodology provides insights for resilient foundation design strategies in challenging coastal environments.